Batas-Batas Penggunaan Fikiran di dalam Mentafsir Al-Quran - Abdullah, Muhammad Zawawi (Jurnal Usuluddin, 1995)
The article discusses the use of aqal in interpreting the meaning of the verses of the Quran.